(untitled) (KULT_online, 2023)
The performative powers and cultural work of fictions have been generally neglected in the academic discourse despite their fundamental role in contemporary society. This edited volume aims at exploring the work and affordances of fictions as well as tracing new and innovative trajectories for literary studies through a collection of case studies and model interpretations